PENINGKATAN KEMAMPUAN MENULIS NARASI MELALUI METODE MIND MAPPING SISWA KELAS V SEKOLAH DASAR - Rahmah Kumullah; Rosdiah Salam; Muh. Faisal (Universitas Sarjanawiyata Tamansiswa, 2019)
This research aims to explain the application of mind mapping method to improve narration writing skills in Indonesian language subject of fifth grade elementary school students. This is a classroom action research, it consists of three cycles and each cycle was conducted in two sessions. The procedures include planning, executing, observation, and reflection. The research focus was mind mapping method implementation and narration writing learning results. This research was conducted in State Elementary School 24 Lapajung, Lalabata District, Soppeng Regency. The research subjects were 1 teacher and 40 students. The data collection techniques involved observation, test, and documentation. The collected data were analyzed using Mile and Huberman’s methods which include data reduction; data presentation; conclusion drawing; and data verification. The research results showed that teacher’s activity in cycle I belong to sufficient category (C), in cycle II it became good category (B), and in cycle III it became very good category (SB). Similarly, in students’ activity, the results showed that in cycle I it belonged to sufficient category (C), and in cycle II and cycle III it increased to very good category (SB). This was followed by an improvement in students’ learning achievements which in cycle I and cycle II belonged to sufficient category (C) became good category in cycle III. Therefore, the mind mapping method implementation can improve narration writing skills in students of State Elementary School 24 Lapajung.